SNOWBALL THROWING TECHNIQUE IN TEACHING RECOUNT TO HELP STUDENTS’ READING COMPREHENSION IN JUNIOR HIGH SCHOOL - Henny Iswati; Duita Cundharani Ridha (Universitas Wiralodra, 2023)
In language learning, reading is crucial for acquiring knowledge and seeking information. Nonetheless, some students may encounter difficulties when it comes to comprehending written texts. In this regard, implementing the Snowball Throwing Technique (STT) can facilitate the teaching and learning process by helping students comprehend the texts effectively. This study focuses on implementing the STT in teaching reading recount text to eighth graders and assesses students' responses to the technique and its impact on their comprehension. This research was conducted descriptively using qualitative design. While collecting data, the researchers did an observation, gave the students two tasks, and interviewed them. The instruments to collect the data are observation checklist notes and interviews. The findings indicate a successful implementation of the technique, with students showing a high level of understanding and expressing ease in comprehending the text. The significance of the study on STT is to offer English teachers valuable knowledge regarding its application for improving students' text comprehension. Furthermore, the researchers recommend future investigations to explore the implementation of STT not only in reading instruction but also across various language skills and sub-skills.